Statistics between winning and losing teams by competition levels and gender in volleyball - Joao, P.; Vaz, L.; Mota, M.; Mesquita, I.; Sampaio, J. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
The identification of sports skills underlying high-level performances can be information of great value to volleyball coaches, thereby allowing them to establish and monitor playing patterns. The aim of this study has been to identify the volleyball game-related statistics that allow for discriminating performances by gender and level of competition. Methods The statistics of all the games (n=344) of the diverse World championships 2007 (including all levels of competition and both gender) were analysed using the Software VIS of the `score box` of the International Volleyball Federation (FIVB), and involved the analysis of the discriminating function (DF) so as to identify the indicators that contribute more to establishing the maximum difference between victories and defeats. Through structural coefficients (SC), we have identified the game-related statistics that better discriminate the levels and genders. Results The results showed that for gender x level of competition the obtained functions in selective analysis were all statistically significant (p<0.05) and classified correctly in 85.6% of the cases. The structure coefficients from Function 1 reflected team faults percentages (SC=0.39), shots spikes percentages (SC=-0.38) and continuity digs percentages (SC=0.31). Function 2 reflected excellent Digs (SC=0.31) and continuity digs (SC=0.31). Function 4 showed team faults percentages (SC=0.35) contribution for discriminating the groups. Function 5 showed the excellent digs (SC=-0.39), the faults receptions (SC=0.35) the faults digs (SC=-0.34) and Serve aces (SC=0.30) contribution for discriminating the groups. For the team faults percentages, it may be observed that there are differences between men and women at different levels of competition. The majority of the teams lose many points through the faults made. It is possible to observe that, in men`s Volleyball, the juniors present elevated team faults percentages, following the same pattern as the seniors and, finally, the youth. In the female Volleyball, the seniors present elevated team faults percentages, the juniors an intermediate figure and the youth present a limited number. Discussion The results show that the use of this study can help coaches to understand better the differences between players - the different genders of players and level of competition - and better regulate training sessions and competition. As the game level increased, so did the risk, because not taking a risk can mean losing a point. In the game of senior Volleyball there is a greater error because continuity may provide an opening for the adversary to score. Men versus women: men fail more probably because they also risk more and in so doing end up by increasing the possibility of losing. It is worthwhile pointing out that the success rate in the attack is almost always higher for seniors, regardless of gender, and decrease gradually until the younger players.